2016
DOI: 10.3109/15622975.2016.1173724
|View full text |Cite
|
Sign up to set email alerts
|

Testing differential susceptibility: Plasticity genes, the social environment, and their interplay in adolescent response inhibition

Abstract: Objectives Impaired inhibitory control is a key feature of Attention-Deficit/Hyperactivity Disorder (ADHD). We investigated GxE as a possible contributing factor to response inhibition variation in context of the differential susceptibility theory. This states individuals carrying plasticity gene variants will be more disadvantaged in negative, but more advantaged in positive environments. Methods Behavioral and neural measures of response inhibition were assessed during a Stop-Signal task in participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 107 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…Finally, given that several studies have shown that gene–environment interactions can be confounded by the presence of gene–environment correlations (rGE; [83,84]), as suggested by Richards et al [85], we primarily carried out Pearson correlation analyses. Then, a hierarchical regression was carried out to verify if children’s DAT1 polymorphisms moderated the relationship between parents’ psychological profile (independent variable) and children’s emotional/behavioral functioning (dependent variable).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, given that several studies have shown that gene–environment interactions can be confounded by the presence of gene–environment correlations (rGE; [83,84]), as suggested by Richards et al [85], we primarily carried out Pearson correlation analyses. Then, a hierarchical regression was carried out to verify if children’s DAT1 polymorphisms moderated the relationship between parents’ psychological profile (independent variable) and children’s emotional/behavioral functioning (dependent variable).…”
Section: Methodsmentioning
confidence: 99%
“…A review of the last 4.5 years of the literature included 34 studies that focused on ADHD diagnosis and related symptoms. A majority of studies focused their environmental exposure on related to psychosocial [67][68][69][70][71][72][73][74][75][76][77], stress and adversity [27,75,[77][78][79][80][81][82][83][84], and trauma-related exposures [85]. Very few focused on toxicant exposure such as blood lead levels [86, 87••, 88], phthalate metabolites [89], and organophosphate pesticide exposure [90].…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…It should be noted that additional susceptibility factors involved in the development of EF that have been found in these mentioned studies include temperamental reactivity (38), physiological reactivity (19), difficult temperament (143), candidate genes such as the 5-HTTLRP, DAT1, DRD4 (20), and neonatal brain volume (18). All these studies suggested that children with susceptibility factors were more sensitive to both negative and positive aspects of the home environment or parenting; children showed poor EF under less optimal environments but outperformed their non-susceptible peers in supportive environments.…”
Section: The Role Of Sensitivity To the Environment In The Developmen...mentioning
confidence: 90%
“…All these studies suggested that children with susceptibility factors were more sensitive to both negative and positive aspects of the home environment or parenting; children showed poor EF under less optimal environments but outperformed their non-susceptible peers in supportive environments. Other environmental aspects that children showed sensitivity to, for better and worst, were adversity and low family income (19,38), maternal behaviors such as sensitivity and the quality of mother-infant interactions (18,143), and peer affiliation (20).…”
Section: The Role Of Sensitivity To the Environment In The Developmen...mentioning
confidence: 99%
See 1 more Smart Citation